2007
DOI: 10.1111/j.1467-6494.2007.00466.x
|View full text |Cite
|
Sign up to set email alerts
|

Religiousness, Spiritual Seeking, and Personality: Findings from a Longitudinal Study

Abstract: The hypothesis that personality characteristics in adolescence can be used to predict religiousness and spiritual seeking in late adulthood was tested using a structural equation modeling framework to estimate cross-lagged and autoregressive effects in a two-wave panel design. The sample consisted of 209 men and women participants in the Berkeley Guidance and Oakland Growth studies. In late adulthood, religiousness was positively related to Conscientiousness and Agreeableness, and spiritual seeking was related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
110
8
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(130 citation statements)
references
References 48 publications
5
110
8
7
Order By: Relevance
“…Third, Wink et al (2007) found that Conscientiousness (␤ ϭ .17, p Ͻ .05) and Agreeableness (␤ ϭ .20 for women, p Ͻ .05; ␤ ϭ .05 for men, ns) in adolescence were associated with in-75 RELIGION, SELF-REGULATION, AND SELF-CONTROL creased religiousness through late adulthood. Fourth, Regnerus and Smith (2005) found that among American youths, religious students with high self-control (i.e., those who eschewed risk taking and who reported making decisions in a deliberative, effortful fashion) remained more religious (as measured by self-rated importance of religion and self-reported frequency of religious service attendance) 1 year later than did those religious students who initially had low self-control.…”
Section: Longitudinal and Experimental Studies Addressing The Causal mentioning
confidence: 92%
See 2 more Smart Citations
“…Third, Wink et al (2007) found that Conscientiousness (␤ ϭ .17, p Ͻ .05) and Agreeableness (␤ ϭ .20 for women, p Ͻ .05; ␤ ϭ .05 for men, ns) in adolescence were associated with in-75 RELIGION, SELF-REGULATION, AND SELF-CONTROL creased religiousness through late adulthood. Fourth, Regnerus and Smith (2005) found that among American youths, religious students with high self-control (i.e., those who eschewed risk taking and who reported making decisions in a deliberative, effortful fashion) remained more religious (as measured by self-rated importance of religion and self-reported frequency of religious service attendance) 1 year later than did those religious students who initially had low self-control.…”
Section: Longitudinal and Experimental Studies Addressing The Causal mentioning
confidence: 92%
“…First, as noted above, McCullough et al (2003) found in a 19-year longitudinal study with data from the Terman study that children high in Conscientiousness (a trait that subsumes self-control) went on to become more religious as adults (␤ ϭ .14), even when background variables influencing religiousness (e.g., being raised in a religious home, gender) were statistically controlled. Second, McCullough et al (2005) found that young adults with low Agreeableness (which is a personality trait reflecting the ability to control oneself out of concern for the feelings and desires of others) manifested a pattern of low religiousness through adulthood.Third, Wink et al (2007) found that Conscientiousness (␤ ϭ .17, p Ͻ .05) and Agreeableness (␤ ϭ .20 for women, p Ͻ .05; ␤ ϭ .05 for men, ns) in adolescence were associated with in-75 RELIGION, SELF-REGULATION, AND SELF-CONTROL creased religiousness through late adulthood. Fourth, Regnerus and Smith (2005) found that among American youths, religious students with high self-control (i.e., those who eschewed risk taking and who reported making decisions in a deliberative, effortful fashion) remained more religious (as measured by self-rated importance of religion and self-reported frequency of religious service attendance) 1 year later than did those religious students who initially had low self-control.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…[23,102,108,113,114]. Importantly, longitudinal studies suggest that people's strategy appears to cause religiousness, rather than religiousness causing people's strategy [115][116][117]. In this perspective, religious beliefs are not part of a life-history coordinated strategy per se.…”
Section: Strategic Moralizing and The Belief In Cosmic Justicementioning
confidence: 99%
“…On one hand, the religious dimension tends to relate to beliefs and practices that are communally and organizationally based, tradition and creed-oriented, and associated with institutional and social pressures (Pepper, Jackson, and Uzzell 2010;Piedmont 1999;Saucier and Skrzypinska 2006;Schlehofer, Omoto, and Adelman 2008;Wink et al 2007;Wink and Dillon 2003;Zinnbauer et al 1997;Zwissler 2007). The spiritual dimension, on the other hand, generally relates to an individual's subjective beliefs and pursuits, is often characterized by a propensity for "spiritual seeking" and personal experiences, includes nontheistic ideas of a higher power and an interest in unorthodox beliefs and practices, and may cooccur with negative feelings towards organized forms of religion (Fuller 2001; Jang and Franzen 2013;Piedmont 1999;Roof 1993;Saucier and Skrzypinska 2006;Schlehofer, Omoto, and Adelman 2008;Wink and Dillon 2003;Wuthnow 1998;Zinnbauer et al 1997).…”
Section: Physician Religiosity/spirituality and Medical Interactionsmentioning
confidence: 99%